2019
DOI: 10.1007/s40261-019-00873-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of a Single Oral Dose of Peficitinib (ASP015K) in Japanese Subjects with Normal and Impaired Renal Function

Abstract: Background and Objective This study measured and compared the exposure and safety of peficitinib (ASP015K), a novel oral Janus kinase inhibitor, in subjects with normal and impaired renal function after a single oral, clinically relevant peficitinib dose. Methods This was an open-label, parallel-group study conducted at two centres in Japan. Subjects with normal and mildly, moderately, or severely impaired renal function received a single oral dose of peficitinib (one 150 mg tablet) under fasting conditions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
(26 reference statements)
2
19
0
Order By: Relevance
“…Peficitinib primarily undergoes metabolism, but approximately 10% is excreted in the urine in the unchanged form. Additionally, the plasma concentration-time profile of peficitinib was similar between individuals with normal and impaired renal function [14].…”
Section: Pharmacodynamics and Pharmacokinetics Of Peficitinibmentioning
confidence: 81%
See 1 more Smart Citation
“…Peficitinib primarily undergoes metabolism, but approximately 10% is excreted in the urine in the unchanged form. Additionally, the plasma concentration-time profile of peficitinib was similar between individuals with normal and impaired renal function [14].…”
Section: Pharmacodynamics and Pharmacokinetics Of Peficitinibmentioning
confidence: 81%
“…Among the five randomized, placebo-controlled trials, two were Phase 2b trials conducted as global studies, one was a Phase 2b trial and one a Phase 3 trial both conducted in Japan, and one was a Phase 3 trial conducted in Japan, Korea, and Taiwan. RA21 was a global, randomized, placebo-controlled Phase 2b trial [14]. In the RA21 study, 387 patients demonstrating inadequate response to methotrexate and prior exposure to TNF inhibitors permitted in North America, including Mexico, Latin America, and Europe received a placebo or peficitinib (25 mg, 50 mg, 100 mg, or 150 mg) in combination with methotrexate for 12 weeks.…”
Section: Efficacy Of Peficitinibmentioning
confidence: 99%
“…Following a single dose of peficitinib 150 mg, the AUC inf geometric mean ratios (GMR) in subjects with mild, moderate, and severe renal impairment versus subjects with normal renal function were 0.87 (90% confidence interval [CI] 0.61-1.25), 0.83 (90% CI 0.58-1. 19), and 1.09 (90% CI 0.74-1.60), respectively [61]. Thus, peficitinib plasma concentration does not appear to be significantly affected by impaired renal function.…”
Section: Interaction Studiesmentioning
confidence: 87%
“…Findings from phase I studies on healthy volunteers demonstrated that peficitinib is rapidly absorbed in fasting condition. Tmax ranged from 1 h to 1.8 h, depending on the dose, and pharmacokinetics was not significantly influenced by renal impairment [ 196 ]. Meals, instead, delay median Tmax from 1.5 h to 4.0 h and increase peficitinib exposure (AUC) by 27% [ 197 ].…”
Section: Second Generation Jakimentioning
confidence: 99%